Ethereum gas price statistics - David Carl; Christian Ewerhart (University of Zurich, Department of Economics, 2020)
For users of the Ethereum network, the gas price is a crucial parameter that determines how swiftly the decentralized consensus protocol confirms a transaction. This paper studies the statistics of the Ethereum gas price. We start with some conceptual discussion of the gas price notion in view of the actual transaction-selection strategies used by Ethereum miners. Subsequently, we provide the descriptive statistics of what we call the threshold gas price. Finally, we identify and estimate a seasonal ARIMA (SARIMA) model for predicting the hourly median of the threshold gas price.
Keywords: C57; C22; D85; E37; 330; Ethereum; gas price; confirmation time; forecasting